Transfer of 238U and 232Th from soils to tea leave sin LuongMy farm, HoaBinh province, Viet Nam - Hoang, Huu Duc (H. : ĐHQGHN, 2020)
The soil-to-plant transfer factors of natural uranium isotopes (238U and 232Th) were studied in Luong My tea farm, Tan Thanh district, Luong Son commune, HoaBinh province. The activity concentrations in leaves, trunk and root were determined for the tea tree at no harvest period (winter break). The measurements were carried out using gamma spectroscopy with high puritygermanium detector HPGe. Research results show that the activity of 238U and 232Th is higher in leaves than in trunk and roots.Soil-leaves transfer factor (TF) for238U and 232Th were as follows:TFU238 = 0,52 – 0,87; TFTh-232 = 0,25 – 0,43.